2019
DOI: 10.1038/s41598-019-42290-y
|View full text |Cite
|
Sign up to set email alerts
|

Helping-Like Behaviour in Mice Towards Conspecifics Constrained Inside Tubes

Abstract: Prosocial behaviour, including helping behaviour, benefits others. Recently, helping-like behaviour has been observed in rats, but whether it is oriented towards rescue, social contact with others, or other goals remains unclear. Therefore, we investigated whether helping-like behaviour could be observed in mice similar to that in rats. Because mice are social animals widely used in neuroscience, the discovery of helping-like behaviour in mice would be valuable in clarifying the psychological and biological me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Cases of rescue behavior are also known in taxa other than ants. These taxa include numerous primate species [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], other mammals [ 68 , 69 , 70 , 71 , 72 , 73 ] and, to date, a single bird species [ 74 ]. The occurrence of rescue actions in such a diverse group of taxa speaks to the generality of the phenomenon and its prevalent importance.…”
Section: Rescue Behavior In Other Taxamentioning
confidence: 99%
“…Cases of rescue behavior are also known in taxa other than ants. These taxa include numerous primate species [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 ], other mammals [ 68 , 69 , 70 , 71 , 72 , 73 ] and, to date, a single bird species [ 74 ]. The occurrence of rescue actions in such a diverse group of taxa speaks to the generality of the phenomenon and its prevalent importance.…”
Section: Rescue Behavior In Other Taxamentioning
confidence: 99%
“…Indeed, research has suggested that empathy for pain or distress is mediated by common neural and neuroendocrine processes in both humans and animals [2,[14][15][16][17][18][19][20][21][22]. Mice and rats may exhibit empathy-related behaviours such as observational fear [23][24][25], social coordination of pain [12], comfort [26], and prosocial support behaviour [27,28]. Several research groups have recognised observational fear as a useful behavioural model for assessing their ability to empathise [2,19,20,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Still, mice can recognize potential genetically attractive (dissimilar at the major histocompatibility complex) mate through odor cues (Penn and Potts, 1999), they are highly prosocial animals demonstrating high-order social interactions (Shemesh et al, 2013) and exhibit a rich repertoire of social behaviors. Moreover, they demonstrate helping-like behavior toward a familiar littermate as well as a novel conspecific (Ueno et al, 2019). This is a behavior that could arise from a desire for social interaction (Silberberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%